Penilaian Siswa Terhadap Kompetensi Kepribadian Guru di Sekolah Menengah Pertama (SMP) Negeri 1 Padang Gelugur - Hana Junesti; Nurhizrah Gistituati (Universitas Negeri Padang, 2023)
This study aim to obtain information student assessment of personality competencies at SMPN 1 Padang Gelugur which can be seen from teacher behavior that can be imitated, teacher emotional stability, teacher responsibility, wisdom. This type of quantitative descriptive research. The research population was students of class VII and VIII SMPN 1 Padang Gelugur with a total of 89 people. The research instrument is a Likert scale model questionnaire with five answer choices. The validity and reliability test showed that the student’s assessment of the teacher’s personality competence was valid and reliable. The research data was processed with the help of the SPSS version 25 program. The results obtained from the data analysis showed 1) the behavior of the teacher who could be imitated was in the high category with a score of 80,22% 2) the emotional stability of the teacher was in the sufficient category with a score of 74.34% 3) the teacher’s responsibility is in the sufficient category with a score of 78.98% 4) wisdom in the sufficient category with a score of 72.1%